Short Communication: Utilization of wild plants in medicinal foods for maternal postpartum recovery among the Kasepuhan in rural West Java, Indonesia - DedeMULYANTO MULYANTO; RIMBO GUNAWAN; SAIFULLAH ZAKARIA; JOHAN ISKANDAR; ATIEK ROSTIKA NOVIYANTI; BUDIWATI SUPANGKAT ISKANDAR (Society for Indonesian Biodiversity, 2024)
Abstract. Mulyanto, Gunawan R, Zakaria S, Iskandar J, Noviyanti AR, Iskandar BS. 2024. Short Communication: Utilization of wild plants in medicinal foods for maternal postpartum recovery among the Kasepuhan in rural West Java, Indonesia. Biodiversitas 25: 465-473. Puerperium is a critical phase. Barriers to access and resource constraints often hinder Indigenous and local communities, resulting in frequently relying on traditional forms of postpartum care, including the utilization of wild plants from surrounding areas. Snowball sampling was utilized to recognize informants who were considered specialists in perinatal care and medicinal foods for maternal postpartum recovery. In-depth and semi-structured interviews were undertaken to gather ethnobotanical data on medicinal foods specially made for maternal postpartum recovery and the utilization of wild plants in their preparation and other therapeutic applications. Collected information included medicinal foods, vernacular names of the plants, plant cultivation status, utilized parts, preparation, and method of administration. Descriptive data was analyzed using ethnobotanical indices. Six different medicinal foods, traditionally consumed by mothers to aid postpartum recovery, were identified. A total of 83 species belonging to 34 families were utilized for respective applications. Out of these 83 species, 41 (49.4%) were classified as wild plants. Arenga pinnata (Wurmb) Merr., Blumea balsamifera (L.) DC., Chloranthus erectus (Buch.-Ham.) Sweet, Coleus scutellarioides (L.) Benth., and Parkia timoriana (DC.) Merr. are wild plants with the highest CVI, and are also used to treat fevers in the study area. Investigations have reported that the bioactive components of these wild plants possess potent analgesic, antioxidant, anti-nociceptive, anti-inflammatory, anti-microbial, and gastroprotective properties. It can be concluded that wild plants hold a significant place in the local knowledge system related to maternal postpartum recovery and other therapeutic uses. Additionally, the practices and acquisition of knowledge for medicinal food preparation are traditionally considered the domain of females.